The Effect of Financial Literacy, Financial Efficiency, and Income on Students’ Investment Decisions in The Capital Market - Naibaho, Ryandri; Sinarasri, Andwiani; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of financial literacy, financial efficacy, and income on students’ investment decisions in the capital market. This research was carried out at the University of Muhammadiyah Semarang. The number of samples taken was 213 active students of the S1 Accounting study program. The sampling technique used is Convienance Sampling or sampling based on convenience. Data collection was carried out by distributing questionnaires through google forms. The data were analyzed using multiple linear regression analysis. Based on the results of the study, it was shown that financial efficiency and income had a positive effect on students’ investment decisions, while financial literacy did not have a significant influence on students’ investment decisions. The results of the study show that financial and income efficacy can improve the quality of investment decisions of students of the S1 Accounting study program at the University of Muhammadiyah Semarang in the capital market.